Acompanhamento da prática pedagógica: representações de estagiários do curso de Licenciatura em Ciências Biológicas da UFSM - Goulart, Sheila Fagundes (2008)
This dissertation was realized on the Formation, Knowledge and Professional Development research line, by the Education Post-Graduation Program (EPGP) of the Universidade Federal de Santa Maria (UFSM), and presents propositions about the beliefs and conceptions that UFSM Biological Sciences Teaching Course trainees have concerning the Supervised Curricular Training (SCT) developed from a training proposal called Attendance in Pedagogical Practice (APP). This Attendance, realized through three basic actions Individual and Collective Consulting (IC and CC), Pedagogical Practice Diaries (PPD) and School Visits (SV), aim at making the training an environment for considering about the teacher s practice, of affirming or not the professional choice and of researching about the teaching occupation practising. The research is characterized by a qualitative approach framed on a case study constructed from watching/participating in the activities performed during the proposal development, the narratives and the documents produced by three trainees. For the analysis and interpretation of the representations about the attendance proposal by the trainees, the works of Freire (1968, 1995, 1997), Riani (1996), Pimenta e Lima (2004), Freitas et al (2005), among others, were utilized. It is important to mention that crystallized conceptions about training are still present in our formation courses and the SCT understanding as a privileged formative environment is a constant quest for the instructors who believe that by sharing experiences and knowledge we become more autonomous professionals.